Two New Species of Semi-Aquatic Freshwater Earthworm Genus Glyphidrilus Horst, 1889 (Oligochaeta: Almidae) from Thailand and Laos - Chanabun, Ratmanee; Jirapatrasilp, Parin; Seesamut, Teerapong; Bantaowong, Ueangfa; Aoonkum, Anuwat; Inkhavilay, Khamla (Tropical Natural History, 2023)
Material of the semi-aquatic freshwater earthworm genus Glyphidrilus Horst, 1889 recently collected from Thailand and Laos contains two new species: G. panhai Chanabun, sp. nov. from Song Khram River, Buengkan, Thailand and G. samueljamesi Chanabun, sp. nov. from Khon Phapheng Waterfall, Mekong River, Champasak, Laos. Morphological characters of both new species are distinctly different from the previous recognized species. Glyphidrilus panhai sp. nov. has wings in 23, 24–29, 30, 31, clitellum in 17, 18–32, 33, 34, 35, and spermathecae in 13/14 (14/15)–18/19. Glyphidrilus samueljamesi sp. nov. has wings in 25, 26, 27–33, 34, 35, 36, clitellum in 18, 19, 20–40, 41, 42, 43, 44, and spermathecae in 13/14 –20/21. Descriptions of all new species including illustrations of the external and internal morphological characteristics are provided.